(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Cloud computing is a defined as a machine that involves delivering hosted services over the Internet. Cloud computing emerges as a new technology shifted from the early techniques such as mainframe architecture to client–server. Cloud computing can be exemplify as fetching third party software and services on internet and paying as per need of individual user. It makes easier scalability and virtualized resources over internet as a service providing cost effective to customers. Cloud computing has proved as a disruptive technology and kick start with the presence of many vendors in cloud computing space. Cloud computing as a substitute for numerous technological approaches and business models such as SaaS, cluster computing, high performance computing signifies that the cloud can be treated as a superset of all the corresponding issues from these paradigms. In this paper we will discuss Life cycle management, Cloud architecture, Pattern in Cloud IDM, Volatility of Cloud relations.